Effect of telmisartan on sub-acute model of inflammation in male Wistar rats - an experimental study - Matule, Somnath M.; Hogade, Anil P.; Kangle, Ranjit P.; A. B., Netravathi; Kolla, Rohan (International Journal of Research in Medical Sciences, 2017)
Background: Cardiovascular diseases remain the major cause of death and premature disability in developed societies.Current predictions estimate that by the year 2020 cardiovascular diseases, notably atherosclerosis and hypertension will become leading global causes of total disease burden. The objective of the study was to investigate the influence of telmisartan on sub-acute model of inflammation in adult male Wistar rats. Methods: After obtaining ethical clearance from Institutional Animal Ethics Committee, animals were allotted to the three groups i.e. control, aspirin and telmisartan (n=6 animals in each group). The effect of telmisartan on inflammation was studied using sub-acute (Cotton pellet granuloma and histopathologic examination of grass piths) models. Experiment was conducted according to the Committee for the purpose of Control and Supervision of Experiments on Animals (CPCSEA) guidelines. Analysis was done using one way ANOVA followed by post hoc tests of Dunnett’s and Bonferroni’s. P<0.05 was considered as statistically significant. Results: In the present study telmisartan showed significant anti-inflammatory activity in sub-acute models of inflammation. Conclusions: In view of role of inflammation in the pathogenesis of atherosclerosis and their complications, treatment by telmisartan can reduce complications by virtue of its anti-inflammatory activity, in addition to its antihypertensive effect. Also this study may help to open new avenues for therapeutic indications of telmisartan.